Antioxidant and Anti-Arthritic Activities of Green Seaweed Halimeda tuna Methanolic Extract - Gazali, Mohamad; Fatimah, Aden Nurin; Husni, Amir; Nurjanah, Nurjanah; Zuriat, Zuriat; Syafitri, Rina (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
Seaweed contains various bioactive compounds rich in pharmacological potentials, such as antioxidants and anti-arthritic. This study aims to determine the antioxidant and anti-arthritic activities of the methanolic extract of Halimeda tuna. Halimeda tuna samples were extracted using the maceration method and methanol. The methanol extract was tested for antioxidant (2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP)) and anti-arthritic activity using denatured bovine serum albumin (BSA). The methanol extract was also subjected to phytochemical and Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Research results revealed that the extract yield was 0.50 ± 0.06%. Phytochemical analysis showed that H. tuna methanolic extract contained flavonoids, steroids, and alkaloids. GC-MS analysis showed that H. tuna methanolic extract contained steroids, fatty alcohols, and fatty acids. The antioxidant activity tests revealed an IC50 value of 299.98 ± 121.15 ppm and a FRAP value of 200.02 ± 8.50 M/g, categorized as a weak antioxidant. Anti-arthritic activity of H. tuna methanolic extract showed an IC50 value of 877.29 ± 209.84 ppm. The anti-arthritic activity of H. tuna methanolic extract was lower than sodium diclofenac as a standard drug. The extract of H. tuna has antioxidant and anti-arthritic activities; hence, further exploration is needed as an alternative potential in the pharmacological field.